An audit of the uptake of key PMTCT interventions in the pre and post WHO rapid advice periods at the University College Hospital, Ibadan (2015)
Prevention of vertical transmission of HIV may require the uptake of the culturally unacceptable options of cesarean delivery and formula feeding. The successful use of HAART, as enumerated by the WHO 2009 rapid advice, has the potential for facilitating the uptake of the more culturally acceptable vaginal delivery and breast feeding. These recommendations became operational at the PMTCT unit, University College Hospital, Ibadan. This retrospective study describes the impact of these recommendations on the uptake of PMTCT interventions at our center. The pre-rapid advice period was June 2009 to April 2011 and the post rapid period May 2011 till December 2012. Pre-rapid advise, antiretrovirals administered was zidovudine or Combivir for women with CD4 The new WHO guidelines appear to have facilitated a shift in uptake of the more culturally acceptable options of vaginal delivery and breast feeding. A follow-up evaluation of the infant HIV status will ascertain the ultimate impact on MTCT. >200cells / ml and Combivir/nevirapine for CD4 <200 Cells/ ml. Post-rapid, all were eligible for HAART (mostly efavirenz/ truvada or efavirenz/ Combivir). Six weeks post-natally, the options adopted were documented and are presented here. Information from 1165 women was available. Thirty three (2.8%) did not have adequate information and were excluded. There were 711 women pre-rapid advise and 421 women post rapid. The women's characteristics were not significantly different over both periods, 69.0% had >6 years of education, 97.0% were married and slightly over half (56.9%) were involved with traders. Overall, more women were delivered by the vaginal route than Caesarean Delivery (70.5% vs. 29.5%), while more breastfed compared to formula feeding (67.2% vs. 32.8%). In the post rapid period (compared to the pre- rapid) advise, more women had vaginal delivery (73.5% vs. 64.8%, p = 0.54), more women breast-fed (77.0% vs. 50.1%, p= 0.00) and fewer women used contraception (21.5% vs. 27.3%, p= 0.023). The commonest method was the condom (83.4%). The new WHO guidelines appear to have facilitated a shift in uptake of the more culturally acceptable options of vaginal delivery and breast feeding. A follow-up evaluation of the infant HIV status will ascertain the ultimate impact on MTCT